Rola działań w zakresie e-zdrowia w obliczu pandemii COVID-19 - Rogalska, Anna; Syrkiewicz-Świtała, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The outbreak of the COVID-19 pandemic had a significant impact on the functioning of healthcare systems around the world. Although digitization activities in healthcare have already been implemented in many countries, they have been significantly accelerated. The aim of the study was to determine the significance of implemented e-health solutions in Poland as a result of the COVID-19 pandemic. The available literature was reviewed: textbooks, scientific articles, legal acts, internet resources, websites of public organizations belonging to the health care system, in order to obtain data on the implementation of e-health in Poland. In Poland, in response to the COVID-19 pandemic, legal regulations were introduced enabling a wider use of telemedicine, including: e-consultations, telerehabilitation, teledidactics, telemonitoring with particular emphasis on the home medical care program. In addition, the activities introduced in the period 2019–2021 in the field of e-health also include: e-prescription, e-referral, online patient account, electronic medical documentation. The COVID-19 pandemic has highlighted the need for e-health measures. The implemented implementations in this area play an important role in reorganization and improvement of healthcare in the current situation. They influence many aspects of the reorganization of the health care system in the face of new management challenges. They contributed to the reduction of patientsʼ exposure to SARS-CoV-2 infection, mitigating the lack of access to traditional health services. However, the proposed solutions should be constantly verified and improved.
Keywords: e-health; COVID-19; public health